Temperament, personality and decision-making accuracy in handball referees - Jacek Świdwa; Magdalena Król-Zielińska; Adam Kantanista (PLoS ONE, 2026)
Accurate decision-making is essential for effective handball officiating, yet little is known about how stable psychological traits relate to referees’ decision-making accuracy. This study examined whether temperament and personality characteristics are associated with decision-making accuracy in handball referees. Forty-one officials from three competition levels (Second League, First League, Superleague) completed the FCB-TI and NEO-FFI inventories. Decision-making accuracy was assessed using a video-based test of game situations scored against expert judgments. Sensory Sensitivity showed a positive bivariate correlation with decision-making accuracy ( r = 0.32, p < 0.05). Multiple regression analysis revealed that competitive level accounted for 24% of the variance in decision-making accuracy ( R 2 = 0.24, p = 0.001). Adding Sensory Sensitivity increased the explained variance to 30%, although its unique contribution did not reach statistical significance. Activity, as a temperament trait, showed different associations with decision-making accuracy across competition levels. No significant relationships were observed between Big Five personality traits and decision-making accuracy. These findings suggest that, among the variables examined, competitive level was the main factor associated with decision-making accuracy, while selected temperament traits, particularly Sensory Sensitivity and, to a lesser extent, Activity, may also be relevant to this outcome.